Direct relationship between protein expression and progeny yield of herpes simplex virus 1 - Moeka Nobe; Yuhei Maruzuru; Kosuke Takeshima; Fumio Maeda; Hideo Kusano; Raiki Yoshimura; Takara Nishiyama; Hyeongki Park; Yoshitaka Kozaki; Shingo Iwami; Naoto Koyanagi; Akihisa Kato; et al. (mBio)
ABSTRACT Although viral protein expression and progeny virus production were independently shown to be highly heterogeneous in individual cells, their direct relationship, analyzed by considering their heterogeneities, has not been investigated to date. To elucidate the direct relationship between viral protein expression and progeny virus production, we constructed a reporter herpes simplex virus 1 (HSV-1) by tagging Venus to the late protein Us11. We then separated the HSV-1-infected cell population into multiple subpopulations according to the fluorescence intensity of Venus—which reflected the expression of L proteins, largely constituting virion structural proteins—and titrated virus yields and performed electron microscopic analysis in each subpopulation. Our results revealed that infectious progeny virus production, as well as nucleocapsid maturation, was triggered only when L protein expression exceeded a specific threshold. This suggested the existence of a rate-limiting step in progeny virus production, with nucleocapsid maturation potentially being one such step.IMPORTANCEEarlier single-cell studies of virus-infected cells have revealed high heterogeneity in the state of viral gene expression and progeny virus yield. Notably, these two aspects have been shown independently, and therefore, the direct relationship between progeny virus production and viral gene expression has been unclear. This study, for the first time, demonstrated the direct and quantitative relationship between viral protein expression and progeny virus production by taking into account their heterogeneities and revealed a threshold for the levels of herpes simplex virus 1 protein expression for progeny virus production, thereby suggesting the existence of a rate-limiting step in progeny virus production.